Sinergi Sekolah dan Keluarga dalam Implementasi Tujuh Kebiasaan Anak Indonesia Hebat untuk Pembentukan Karakter Religius Siswa - Thein, Anselmus; Lorensius, Lorensius; Nacia Jeo, Sofia; Rasia Erlita, Eupha; Eva Jelau, Jesika (LP3M, Universitas Muhammadiyah Kendari, 2026)
This study aims to describe the form, process, and impact of collaboration between Catholic Religious Education teachers and parents in implementing the Seven Habits of Great Indonesian Children in Catholic elementary schools in Samarinda. The study employs a descriptive qualitative approach through a case study design involving eight informants consisting of Catholic Religious Education teachers, the principal, and parents. Data were obtained through in-depth interviews, limited participatory observation, and the review of school and church documents. The findings show that collaboration emerges through intensive and directed communication between teachers and parents that supports the alignment of children’s faith formation. Three significant outcomes are highlighted. First, regular communication enables effective coordination in prayer routines and liturgical activities. Second, family involvement in spiritual guidance at home strengthens the consistency of the seven habits. Third, the synergy between school and church yields concrete improvements in students’ spiritual discipline, faith responsibility, and religious character. The study affirms that sustained collaboration between teachers and parents is a strategic foundation for strengthening faith education in Catholic elementary schools.